Understanding contemporary India - "Vanaik, Achin. (ed.)" (New Delhi, 2010)
Understanding Contemporary India: Critical Perspectives brings together contributions from scholars and teachers of the Department of Political Science, University of Delhi. This Reader examines the peculiarities of Indian democracy the character of its political institutions and patterns of governance and the remarkable paradoxes that co-exist in what is easily the most diverse society in the world perceived from whatever angle one chooses socially, culturally, geo-ethnically, politically and intellectually. The widespread belief that India is an emerging power on the world stage cannot hide the fact that India faces many grave problems and difficulties even as it is equipped with significant material and cultural resources to tackle them. This collectively agreed project deals with the central issues which confront India today.
Keywords: India-Political and social aspects